The examination of conservation awareness, future sustainability, and conservation readiness on tourists’ attitude towards marine conservation behavior in Malaysia’s Marine Parks - Abdul Latif, Samshul Amry; Yazid, Farah Nadhirah; Mohd Farudz, Baiduri Zaiyyanna (IOP PUBLISHING, 2024)
This study examines the relationship between tourists' conservation awareness, future sustainability, and conservation readiness towards attitude toward marine conservation behavior in Malaysia's marine parks. This study adopted the quantitative convenience sampling approach, with 202 samples obtained via an online questionnaire. IBM-SPSS version 26 was used to process and analyze the data. Multiple Regression Analysis was used to test the relationships between variables. The findings suggest that future sustainability and conservation readiness are significant factors in predicting tourists' attitudes towards marine conservation behavior. In contrast, conservation awareness was found to be insignificant. This study found that respondents have a positive attitude towards marine conservation behaviors, but awareness does not always translate into action. This study found that respondents support marine conservation and marine park sustainability. Awareness of conservation efforts does not necessarily lead to positive attitudes towards conservation behavior. The impact of conservation readiness on attitude emphasizes the need for preparation and education in conservation. The unexpected possible relationship between education and conservation behavior warrants further investigation. These findings highlight the importance of focused conservation education and the necessity to consider many elements when increasing stakeholder marine conservation behavior.